Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 2 - Section 2.3 - The Algebra of Functions - Exercise Set - Page 133: 62



Work Step by Step

$f(2)=0, g(2)=1, f(0)=-2, g(0)=4$ $(fg)(2)=f(2)g(2)=0\times1=0$ $(\frac{g}{f})(0)=\frac{g(0)}{f(0)}=\frac{4}{-2}=-2$ $(fg)(2)-((\frac{g}{f})(0))^{2}=0-(-2)^{2}=0-4=-4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.